Analisis Turnover Karyawan untuk Perancangan Employee Engagement di PT X - Priscilla Angelica (Jurnal Titra, 2019)
PT X is one of the multinational companies in Indonesia that is engaged in consumer goods sector. This company houses around 30,000 employees spread throughout Indonesia. In the past two years, employee turnover has become one of the problem issue at PT X. The average employee turnover rate from 2016-2018 reaches 10-15%. This high level of turnover indicates that relationships between the company and employees are not well established. The company wants to improve this relationship by increasing employee engagement. The thing that needs to be done by the company is knowing the reasons and characteristics of employees first to determine the right employee engagement system/program/….. Reasons for employees were identified by exit questionnaire and analyzed using Pareto and 5 Whys Analysis. The characteristics of employees were analyzed by Chi-Square to determine the relationship of each characteristic on the employee's reasons. The results are then used as a consideration to determine and design employee engagement that appropriate to the needs and conditions of employees. This employee engagement proposal is expected to improve good relations between the company and employees so that trust, loyalty and dedication can be established.